TO DISCUSSION OF THE SPECIFIED METRICS OF THE FIRST APPROACH OF THE ROTATING SPHERE IN THE MECHANIC GTP - Abdildin, М.М.; Taykenova, А.S. (Recent Contributions to Physics, 2017)
In work the further discussion of structure of the metrics of a rotating sphere is spent.